Implementasi Kebijakan Keterbukaan Informasi Publik pada Pejabat Pengelola Informasi Dokumentasi (PPID) di Dinas Komunikasi Informasi Sandi dan Statistik Kabupaten Pandeglang - Fauziah, Lia; Amiruddin , Suwaib (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2024)
The principle of good governance requires accountability, transparency, and public participation in every process of public policy that requires every public agency to provide public information services. The government's obligation to implement transparency or openness of public information is then regulated in Law Number 14 of 2008 concerning Openness of Public Information. This study aims to determine the implementation of the public information disclosure policy at the Documentation Information Management Officer (PPID) at the Pandeglang Regency Communication and Information Service Office. The public policy implementation model used according to George C. Edward III includes aspects of resources, communication, bureaucratic structure, and disposition (Tahir, 2014:61). The research method uses a descriptive method with a qualitative approach. The informants of this study consisted of elements of the Pandeglang Regency Communication and Information Service Office, elements of the Pandeglang Regency OPD, and the community as applicants for public information. The results of the study showed that the implementation of the public information disclosure policy at the PPID at the Pandeglang Regency Communication and Information Service Office in general was good and only needed improvement in several factors. There is a shortage in resource factors as indicated by the goods and services expenditure items, namely the absence of printing expenditure for the procurement of banners, and service expenditure for the implementation of outreach to the community.. The communication factor had shortcomings, there was no socialization to the community, both direct and indirect socialization. The Bureaucratic structure factors lack SOP, the service process time limit is considered quite long. Disposition factors lack of updating public information on the PPID Website of Pandeglang Regency